Glutathione-S-transferase activity of Fucus spp. as a biomarker of environmental contamination - Cairrão, E.
Coastal zones are important areas from both ecological and economical points of view. However, in the last decades, in several regions of the globe, they have been increasingly impacted by complex discharges of contaminants and by marine traffic accidents. The Portuguese Atlantic coast is particularly exposed to these contaminants due to the proximity of important navigation routes. Several rocky shore organisms have been tested and used as bioindicators of environmental contamination. However, to the best of our knowledge Fucus spp., which are key species in rocky shore communities, have not been used as bioindicators in monitoring studies based on biomarkers. The objective of this study was to investigate the potential of glutathione-S-transferase (GST) activity of several Fucus species (Fucus ceranoides, Fucus spiralis var. platycarpus, Fucus spiralis var. spiralis and Fucus vesiculosus var. vesiculosus) to discriminate sites with different contamination levels along the Portuguese Northwestern coast, between the Minho river estuary and the Aveiro's Lagoon, as an environmental biomarker. With the exception of F spiralis var. spiralis, for which a confusing pattern of activity was found requiring further analysis, all the other species and varieties showed higher GST levels in more contaminated sites than in less contaminated ones, indicating that Fucus spp. are suitable for use as bioindicators and their GSTs as biomarkers of environmental contamination in coastal zones and estuaries. (C) 2004 Elsevier B.V. All rights reserved.